TO THE PROBLEM OF GENRE CLASSIFICATION OF FOLKLORE PROSE OF KARACHAYS AND BALKARIANS - F. H. GULIEVA (ZANUKOEVA) (Кавказология, 2019)
Article is devoted to research of some aspects of one of the most important and actual problems of karachay-balkarian folklore study – genre and intragenre classification. Despite of presence of generalizing works and some researches in this area, it cannot be considered solved up to the end. The schemes, used today, borrowed in due time from russian folklore study, don't quite correspond to the national material. So, for example, at division of oral prose into fairy-tale and unfairy-tale some types of works fall out (fables, fiction), others, on the contrary, being divided into two groups, join to both types and represent boundary genres (parables, anecdotes). The similar phenomenon is observed also at attempt of intragenre classification. In philological science it is traditionally accepted to allocate household, magic and animalistic fairy-tales, however upon deeper study scientists reveal also other versions (mythological, heroic, magic-heroic). Besides there remains opened a question about where to carry philosophical fairy-tales with parable nature and a fairy-tale-riddles of type «Who is bigger?», «Who is stronger?», the genre accessory of hunting tales  also raises the doubts. Solution of the problem is also complicated by genetic link and diffusion of various genres. In accordance with carried out research, in the end is made the conclusion about an indispensability of adaptation and improvement of existing classification schemes, based directly on the specifics of national folklore material.